An alternative universe? Authors as copyright owners- the case of the Japanese Manga Industry. Issue 1 (2nd January 2019) - Schroff, Simone
Abstract: Comics today are a major business and they form the source material for a whole range of sectors in the creative industries. In an environment where major investments are necessary to turn a comic into a cross-media success, commercial intermediaries such as Disney have become the key copyright holders. By controlling the copyright, they ensure full control over all aspects of its monetisation. However, this is not the only way success can be achieved on a commercial scale. In Japan, the creators of comics (Mangaka) keep their copyright- a direct contradiction to current copyright thinking. This paper addresses this conundrum by examining both the Manga business and copyright law to identify if the reasons why copyright is not centralised in the hands of the commercial intermediary, especially the publishers. The analysis will show that while there are differences between Japan and the EU/US, but these do not affect the role of copyright law and indeed failing to acquire the rights is a choice, not a necessity. Instead, this article will highlight that the competitive Manga market in combination with the uniquely Japanese publication right and social control best explain why Mangas are successful and Mangaka keep their rights.